Rancang Bangun Sistem Informasi dan Monitoring Level Stress Penderita Diabetes Millitus (DM) Berbasis Android (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2018)
Diabetes Mellitus (DM) is a metabolic disorder with low insulin absorption. The impact of disease is the increasing in the body glucose concentration (hyperglycemia), and most importantly disturb the psychological sufferers, namely stress effect. Stress effects of diabetes mellitus patients have a bad impact for them, such as decreasing endocrine system which is can increase blood levels. In addition, the effect of patient can behave negatively. Therefore, we propose an expert system to solve the problem of diabetes mellitus patient. Thus the patient can analyze and observe stress levels immediately. Our proposed method uses a questionnaire of DASS (Depression Anxiety Stress Scales) 42 form to monitor the level of stress (normal, light, moderate, heavy, very heavy) using mobile applications. Based on our experiment with 30 sample patients in Cerme South Village Clinic, Gresik, East Java, Indonesia, the level of diabetes patients is about 97% normal and 3% light stress. Keywords— Diabetes Millitus, DASS 42 Scale , Stress Level, Mobile Application